Human exposure assessment of airborne pollutants for residents in gwangyang city near industrial plants (I) - Kim, Jae Hyoun; Ahn, Ryoung-Me; Kim, Tae Jong; Lee, Kyoungho; Son, Bu-Soon (Toxicology and Environmental Health Sciences, 2018)
Objective The object of this study is to analyze metabolites of environmental chemicals and to identify possible health hazards to obtain reliable levels of exposure in Gwangyang city in the vicinity of a refinery and steel industrial complex in the year 2011-2012. Methods Participant age in each gender was significantly >59 years comprising more than 90% of the total participants and female participants were almost double males. Target metabolites included 21 chemicals of 3 heavy metals, 4 polycyclic aromatic hydrocarbons (PAHs), 7 volatile organic compounds (VOCs), 5 phthalates and creatinine. Results We found some interesting points of comparison. The geometric mean values of metabolites in control area were similar to or slightly higher overall than those in the exposed area. Some metabolites, such as urinary (U)-Hg and organic metabolites like VOCs, PAHs and phthalates, significantly showed higher concentrations in the control area. Whilst their highest (max.) values for three metabolites (U-m-methylhippuric acid (MHA), U-p-MHA and U-monobenzyl phthalate) in the exposed was always higher than the control. Moreover U-Cadmium, U-2-Naphtol and U-ttmuconic acid (MA) in the exposed area far exceeded the national average and average of 50+ age group. Interesting gender-specific differences in three VOC metabolites (U-t,t-MA, U-hippuric acid (HA), U-mandelic acid (MA) (female specific, females>males) and blood (B)-lead (Pb) (male specific, males>females) were seen, and were always higher in males or females in both areas. Accordingly, the present study indicates that heavy metals and VOCs appear to be the most noteworthy pollutants that may cause adverse health effects in the human population near Gwangyang city. Conclusion In conclusion, observed metabolite levels did not exceed health-based reference values and/or guidelines available. Nevertheless, continuing biomonitoring surveillance is necessary to watch on hazardous air pollutants (HAPs) to protect public health in industrial sites.